Effect of Massage and Bathing or Swimming toward Baby Weight Improvement - Nurin Fauziyah; Ratna Feti Wulandari; Luluk Susiloningtyas (Universitas Islam Bandung, 2022)
Body weight or anthropometric measure is the most important and most frequently used measure to see the development of infants. Stimulating the growth in infants aged 4 to 6 months can be done in two ways: massage the baby's body and continue by bathing or swimming. This study aimed to analyze the effect of massage and bathing or swimming on an infant's weight gain in Kinara Mom and Baby Spa, Kerkep village, Gurah district, Kediri regency. The research design is quasi-experimental, with one group pre-test-post-test design approach, carried out in August–October 2021. The sample was babies aged 4–6 months using purposive sampling with a sample size of 20 babies—independent variables were baby massage and bathing or swimming on infants, and the dependent variable was weight gain. The instrument used is a weight-monitoring sheet. Data were analyzed using pairs sample t-test analysis. The results showed that all 20 babies experienced weight gain. The conclusion is that massage and bathing or swimming affect weight gain in infants aged 4–6 months.